PHILOSOPHY OF TECHNOLOGY IN THE ХХ1 CENTURY: MODERN STATE AND PERSPECTIVES - E. E. El'kina (Дискурс)
The article regards the reasons of the crisis in the field of philosophy of technology and the new approaches to technology investigation on the basis of synthesis of subject-object principles of knowledge and practice and inner techniques to develop human subjective world and to create subjective ontologies.